Faculty development begins with our students: A framework for students to build their educator portfolio - Melanie Fentoullis; Annette Burgess; Megan Kalucy (2023)
Background Health professional students and junior healthcare professionals contribute significantly to the teaching ‘workforce’. On graduation, health professionals are expected to supervise, teach, assess and provide feedback to their colleagues, from both within their own discipline and across disciplines within health (Burgess & McGregor, 2018), with these skills increasingly listed internationally as graduate attributes. Student-as-Teacher training is emerging across the globe. Recent literature-informed recommendations for Student-as-Teacher curricula focusses on the duration, content, and delivery of programs; feedback and assessment of students’ teaching skills; and approaches to the evaluation of the teacher training programs. Professionalism includes self-awareness and self-reflection and requires health professionals to reflect regularly on and refine their practice and its effectiveness (Medical Board of Australia, 2020). However, there is a paucity of evidence demonstrating how students can develop their own professional portfolios as educators. Workshop Outline In this workshop we discuss the rationale for developing students’ skills to evaluate their teaching and record their progress. We explore how Student-as-Teacher programs can implement frameworks that can be strategically prioritised to maximise student engagement in professional recognition opportunities (such as the Advance HE Fellowship), career mobility and development. This workshop aims for participants to evaluate novel scaffolded frameworks that will assist their students to build their professional portfolio as an educator. The portfolios will be designed to evidence teaching skills and practice and identify areas for improvement. Participants are encouraged to consider how a portfolio framework can be applied in their context to enable student opportunities for professional recognition as educators. References Burgess, A., McGregor, D. Peer teacher training for health professional students: a systematic review of formal programs. BMC Med Educ 18, 263 (2018). https://doi.org/10.1186/s12909-018-1356-2 Medical Board of Australia. Good medical practice: a code of conduct for doctors in Australia. (2018). https://www.medicalboard.gov.au/codes-guidelines-policies/code-of-conduct.aspx